Restricted or absent immune responses in human populations to Plasmodium falciparum gamete antigens that are targets of malaria transmission-blocking antibodies (The Rockefeller University Press, 1989)
We have studied the antibodies to sexual stage antigens of Plasmodium falciparum in human sera from Papua New Guinea where intense transmission of P. falciparum occurs as well as the less prevalent P. malariae and P. vivax. In extracts of gametes of P. falciparum we have studied the reactivity of serum antibodies with antigens labeled with 125I on the surface of the gametes as well as intracellular gamete antigens. A prominent 27-kD sexual stage-specific intracellular protein was recognized more or less in proportion to the general antibody response to gamete proteins. The response to the gamete surface proteins, however, was quite unrepresentative of the general antibody response to the intracellular gamete proteins. No antibodies were detected against Pfs25, a 21-kD protein expressed on zygotes and ookinetes of P. falciparum and known to be a sensitive target of malaria transmission-blocking antibodies. The antibody response to two other target antigens of transmission-blocking antibodies on the surface of gametes of P. falciparum, a 230- and a 48- and 45-kD protein doublet, was very variable and independent of the response to the internal protein antigens. Several possibilities are discussed that may account for the variable response to these gamete surface antigens in individuals with otherwise good antibody responses to internal sexual stage proteins. Among these is the possibility that there is MHC restriction of the immune response to the gamete surface antigens in the human population. This interpretation accords well with evidence for MHC-restricted immune response to the same P. falciparum gamete surface antigens in studies with H-2 congenic mice (24).